2017
DOI: 10.1002/jum.14417
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Ultrasonographic Parameters in Confirmation of Carpal Tunnel Syndrome

Abstract: Results of the study show that the mean cross-sectional area and inlet cross-sectional area may be valid and easy-to-acquire parameters for routine clinical use in confirming CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 45 publications
(100 reference statements)
1
58
0
Order By: Relevance
“…4 Many studies used bilateral observations of single participants, treating each wrist individually in the statistical analysis. 3,5,10,[12][13][14][16][17][18][19] The participant characteristics (age, height, weight, body mass index, and gender ratio) of all 21 studies are summarised in Table 1. Many studies specified the mean age and male-to-female ratio of both case and control groups, with matching of case/controls in 13 studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Many studies used bilateral observations of single participants, treating each wrist individually in the statistical analysis. 3,5,10,[12][13][14][16][17][18][19] The participant characteristics (age, height, weight, body mass index, and gender ratio) of all 21 studies are summarised in Table 1. Many studies specified the mean age and male-to-female ratio of both case and control groups, with matching of case/controls in 13 studies.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10] Electrodiagnostic testing is considered by authors to be an accurate test, with a sensitivity and specificity of 78-95% and 80-95%, respectively. 1,11,[12][13][14] However, other authors have reported varying false-negative rates of 10-34%. 2,[6][7][8][9] The test assesses for physiological delays within the median nerve through slowed electrical conduction due to compression, representing the degree of inflammation and axon loss.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations